Information communication technology integration via Bloom’s taxonomy in accountancy curriculum - Olive Stumke (Transformation in Higher Education, 2023)
Accountants should stay relevant to the business world, making Information Communication Technology (ICT) competencies essential, as highlighted by professional bodies and employers. For this reason, how and when ICT competencies can be integrated into the accountancy curriculum following the guidelines of Bloom’s taxonomy was investigated. ICT competency integration into the accountancy curriculum remains a challenge at South African universities, further highlighted by online teaching during the COVID-19 pandemic. This research followed a qualitative approach. Data collection was done through a literature review of Bloom’s taxonomy, ICT requirements from the South African Institute of Chartered Accountants (SAICA) and employers, responses from a self-developed questionnaire from lecturers of two participating universities focusing on the perceived inclusion of ICT competencies and when these competencies should be taught in the accountancy curriculum. The participants agreed with the inclusion of MS Excel and MS Word with a discrepancy of when.